Neoliberalism and education in Russia: global and local dynamics in Post-Soviet education reform - Minina, E (2014)
This dissertation examines the socio-cultural underpinnings of neoliberal educational reforms vis-à-vis the national educational settings in Russia. By drawing upon NVivo-aided Discourse and Frame analysis as a methodological path, this study critically examines a corpus of state laws on education and official government statements from 1991 to 2012 in contrast to contemporary societal discourse on education, where novel and indigenous educational meanings have been contested and re-negotiated. This thesis shows how the conceptual mélange of global neoliberal ideas has been interpreted, institutionalised and resisted in Russia by exploring the semantics of key neoliberal reform ideas - ‘quality assurance,’ ‘educational standards,’ and ‘commercial educational service’ - at the micro-level of policy texts, political debates and public discussions. This thesis shows that having heralded an educational revolution, the official reform narrative rhetorically endorsed neoliberal orthodoxy, while continuing in practice to discursively draw on pedagogical and administrative frameworks which it previously renounced as outdated. In communicating the spirit of radical neoliberal modernisation, the Russian government rhetoric has collectively embraced a number of contradictory concepts, slogans and directives that have never been harmonised in a unified reformatory framework. The study also argues that the public interpretation of neoliberal concepts has been radically different from the intended conceptualisations offered by the global international stakeholders and conveyed by the Russian educational elite. It shows how, when interpreted through the lens of local pedagogical values, the semantics of global modernisation templates, such as ‘educational quality’ and ‘educational standardisation,’ took on unexpected, culturally-specific, meanings. It also finds that the newly introduced principles of entrepreneurship, self-interest, consumer choice, self-responsibility and competition, which underlie the neoliberal economic reform, remained in opposition to fundamental principles of Russian culture, such as communalism, egalitarianism, state paternalism and anti-monetarism. By unpacking opposing ideological and pedagogical frames, this thesis explains the cultural aspects of the widespread public resistance to post-1991 education reform in Russia. This dissertation seeks to enhance the understanding of the policy formulation process and interpretation of global neoliberal ideas from both top-down and bottom-up perspectives. By advancing a culturalist approach to policy analysis, the present study addresses an overlooked piece of the long-standing puzzle of perceived post-Soviet educational crisis, supplementing the broader scholarly discussion on the successes and failures of neoliberal reforms in the post-Soviet space.